Kekerasan Seksual Pada Remaja - Intan Fadilah Nasution; Ferdy Muzzamil; Salwa Azzharah; Aura Islamyazizah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Sexual violence is deviant sexual behavior that can affect the health and life of the victim. Various studies show that teenagers are vulnerable to experiencing sexual violence, both from people they know and strangers. This literature review research on 10 articles on the internet aims to understand more about sexual violence against teenagers. Based on the results of the literature review, it was found that sexual violence against adolescents can occur in various forms, such as rape, molestation, sexual harassment, or sexual exploitation. Research also shows that risk factors for sexual violence in adolescents include a disharmonious family environment, previous experiences of violence, conflicting lifestyles, and low levels of education. Sexual violence in adolescents can have short-term and long-term impacts on the health and well-being of victims. Short-term impacts include physical, emotional, and psychological injuries, while long-term impacts can include psychological disorders, including depression, anxiety disorders, post-traumatic stress, and suicidal ideation. To reduce the risk of sexual violence in adolescents, there needs to be ongoing prevention and education about healthy sexuality and social responsibility in respecting human rights and respecting human dignity. Prevention can be carried out at the individual, family and community levels, including providing counseling support to victims and providing rehabilitation and recovery services.